Coefficient estimates for a subclass of analytic functions by Srivastava-Attiya operator - JAFARI, Mostafa; MOTAMEDNEZAD, Ahmad; ANALOUEI ADEGANI, Ebrahim (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper, we investigate bounds of the coefficients for subclass of analytic and bi-univalent functions. The results presented in this paper would generalize and improve some recent works and other authors. Mathematics Subject Classification (2010): 30C45, 30C50. Received 19 December 2019; Accepted 08 January 2020.